KNOWLEDGE AND ADOLESCENT ATTITUDE OF SMK COKROAMINOTO MANADO ABOUT REPRODUCTIVE HEALTH - Susanti V. Umar; Monica S. Tandiayuk; Nurseha S. Djaafar (POLTEKKES KEMENKES MANADO, 2018)
Background: Knowledge of reproductive health for adolescents is very important. Based on the nursing problems at the Cokroaminoto Manado Vocational School found in interviews with 5 female students, it shows that female students do not yet know about problems that often occur in reproductive health such as sexually transmitted diseases (STDs) and how to maintain healthy hygiene reproduction. Objective: This study was to determine the relationship of knowledge with adolescent attitudes about reproductive health at SMK Cokroaminoto Manado. Method: This type of research is analytic with a cross-sectional approach using a total sample technique to obtain 30 female teenage respondents at the time of the study. The statistical technique used is the Chi-square test with significance value ≤0.05. Measuring instruments used are knowledge and attitude questionnaires. Results: The test results obtained by the Pearson Chi-square test obtained value x ² = 15,200 with p (asmp.sig) = 0.001 <0.05 means significant, so H0 is rejected and Ha is accepted. Conclusion: There is a relationship between knowledge and adolescent attitudes about reproductive health at SMK Cokroaminoto Manado. Suggestions for young women to seek more information about reproductive health so that the knowledge of adolescent girls increases.